2021
DOI: 10.1055/a-1283-6422
|View full text |Cite
|
Sign up to set email alerts
|

Verbesserung der psychischen Gesundheit und Bindung bei postpartal psychisch erkrankten Frauen – Evaluation einer interaktionszentrierten Therapie in einer Mutter-Kind-Tagesklinik

Abstract: Zusammenfassung Ziele Frauen mit postpartalen psychischen Störungen zeigen häufig eine verzögerte Bindungsentwicklung zum Kind mit negativen Folgen für die kindliche Entwicklung. In mehreren Ländern wurde nachgewiesen, dass eine spezifische Mutter-Kind-Behandlung positiv auf die mütterliche Psychopathologie und die Bindungsentwicklung wirkt. Daten für den deutschsprachigen Raum sind rar, auch aufgrund … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…The mothers in our sample were admitted from May 2010 to August 2021. All mothers were treated with their infants in a multimodal day-care setting including family therapy, video intervention therapy, group psychotherapy, cognitive behavioral therapy, medical treatment, and counseling on childcare ( 36 ). Data of 379 women were available for the indicated period.…”
Section: Methodsmentioning
confidence: 99%
“…The mothers in our sample were admitted from May 2010 to August 2021. All mothers were treated with their infants in a multimodal day-care setting including family therapy, video intervention therapy, group psychotherapy, cognitive behavioral therapy, medical treatment, and counseling on childcare ( 36 ). Data of 379 women were available for the indicated period.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, our results align with the study by Muzik et al ( 2013 ), who also found an important role for maternal psychopathology in the CM-bonding relationship. Together, these results highlight that supporting mothers with postpartum depressive symptoms represents an important prevention pathway (Chamberlain et al, 2019 ; Weidner et al, 2021 ) and could help reduce the impact CM experiences can have on the affective mother–child relationship. Findings can also be seen from the perspective that even if a mother experienced CM, this may not causally determine her bond to her child.…”
Section: Discussionmentioning
confidence: 77%
“…However, our study provided promising preliminary evidence that in addition to overall CM, emotional neglect may be particularly relevant for mother–child bonding in the early postpartum period. Consequently, assessing maternal emotional neglect history in perinatal care could help identify mother–child dyads at risk and thus implement targeted prevention strategies (Weidner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the treatment of postpartum mental disorders, including mother–infant BD, focusing on the mother–infant dyad is possible and effective for both the mother and child. It should explicitly include the processing of the birth experience ( 55 , 75 77 ).…”
Section: Discussionmentioning
confidence: 99%